2018
DOI: 10.1002/app.46597
|View full text |Cite
|
Sign up to set email alerts
|

Influence of thermal and morphological characteristics on mechanical responses of polypropylene/γ‐irradiated elastomer blends

Abstract: The approach of this paper is to examine the mechanical responses of polypropylene (PP)/γ‐irradiated ethylene acrylic elastomer blends and subsequently compare them with the PP/unirradiated ethylene acrylic elastomer blends. Thorough correlations were drawn between the mechanical characteristics of blends and their morphological, thermal, thermomechanical, and fractured surface morphological aspects. The idea of carrying out γ‐irradiation was to introduce crosslinking points in the elastomer phase. For better … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
4
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 50 publications
1
4
0
Order By: Relevance
“…The oversized PGA particles with poor interfacial adhesion caused defects in the PETG matrix that induced the formation of cracks, which developed rapidly under tensile stress. Similar experimental results have also been reported for many other blends [ 18 , 19 , 20 ].…”
Section: Resultssupporting
confidence: 90%
“…The oversized PGA particles with poor interfacial adhesion caused defects in the PETG matrix that induced the formation of cracks, which developed rapidly under tensile stress. Similar experimental results have also been reported for many other blends [ 18 , 19 , 20 ].…”
Section: Resultssupporting
confidence: 90%
“…For the lithiation process, the EVA colloids are stretched to accommodate the porous Si expansion. The deformation of EVA colloids adsorbs the energy caused by the volume change of porous Si, impeding the cracking of PAA molecular chain. The shaped EVA colloids recover to almost original state after the delithiation process.…”
Section: Resultsmentioning
confidence: 99%
“…However, the difference in |G*| value of P-50AE/200 and rest compositions were very minimal. In our previous study, 34 it was observed that the η* and |G*| were lower for the blends with a lower concentration of uncrosslinked elastomers, that is, 5 and 10 wt.% and eventually the foamability was also greater for these two compositions. The opposite trend of complex viscosity and vGP plot is attributed to the lower viscous modulus (G″ = G′ × tanδ) of P-50AE/200 in comparison to the P-12.5AE/200 owing to the crosslink formation inside the elastomer chains, which actually restricted the flow of the P-50AE/200 blend.…”
Section: Resultsmentioning
confidence: 78%
“…The viscosity reduction of blends with elastomer having a higher extent of crosslinking is attributed to the more disintegration of crosslinked elastomer domains into smaller domains and easier slippage of them over the PP melt abiding by the action of ball bearing effect. 34 As already discussed in our previous article, 34 that crosslinked elastomers have a tendency to fragment within the blend contrary to non-irradiated elastomer phases in the PP blends. These fragmented irradiated elastomeric domains might be slipping past the PP phase at the interphase between the elastomer and PP.…”
Section: Rheological Characterizationsmentioning
confidence: 76%
See 1 more Smart Citation